FORMATION OF THE COMPANY'S STRATEGY IN THE CONDITIONS OF A DYNAMIC BUSINESS ENVIRONMENT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the specifics of the functioning of a dynamic business environment, which stimulates enterprises to constantly adapt to changes and form effective strategies to ensure their profitability. The process of forming the company's strategy in the conditions of constant changes in the business environment is studied. The key aspects of the formation of the company's strategy are analyzed, in particular, the identification of factors of the external environment that affect business processes, the analysis of internal resources and competitiveness, as well as the principles of determining strategic goals and action plans. Methods and tools that help enterprises effectively adapt to changes, such as SWOT analysis, PESTLE analysis, portfolio analysis and others, are considered. The importance of constant monitoring and strategic planning to ensure the conditions of sustainable development of the economic entity is determined. Recommendations for the formation of an enterprise strategy in the conditions of a dynamic business environment are offered. The importance of adapting and constantly updating the company's strategy is proven, which is defined as a key factor of successful activity in modern conditions. The need for active strategic planning of the economic activity of enterprises and their adaptation to the changes that are constantly occurring in their business environment, in order to achieve a competitive advantage and sustainable development, is determined. It has been proven that in order to achieve success on the market in conditions of significant dynamics of business processes, it is necessary to take into account not only current trends, but also possible future changes in the environment itself, which requires an enterprise to be open to innovation and ready to take risks. It was determined that innovation and flexibility are important elements of the company's development strategy, allowing it to quickly respond to changes and occupy new markets. The peculiarities of the formation of the business entity's development strategy in the conditions of a dynamic business environment, which requires it to combine traditional strategic approaches and innovative ideas, are considered. It was determined that the involvement of all levels and units of the organization in the process of strategic planning is an important aspect of the formation of the company's development strategy in the conditions of a dynamic business environment. At the same time, communication and cooperation between structural divisions, the ability to effectively exchange information become the basis for the successful implementation of the chosen strategy.
Keywords: enterprise strategy, business environment, business processes, market dynamics, strategy formation.